2007
DOI: 10.1111/j.1745-7270.2007.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Calprotectin: Effect of Calcium and Zinc on its Secondary and Tertiary Structures, and Role of pH in its Thermal Stability

Abstract: Calprotectin, a heterodimeric complex belonging to the S100 protein family, has been found predominantly in the cytosolic fraction of neutrophils. In the present study, human calprotectin was purified from neutrophils using two-step ion exchange chromatography. The purified protein was used for circular dichroism study and fluorescence analysis in the presence of calcium and zinc at physiological concentrations, as well as for assessment of its inhibitory activity on the K562 leukemia cell line. The thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
1
35
1
Order By: Relevance
“…Purification and Use of Calprotectin from Human Neutrophils-Calprotectin was purified from the cytosol of human neutrophils obtained by nitrogen cavitation using a previously described method (14) with Coomassie Blue staining of reducing SDS-PAGE gels indicating that the purity of calprotectin was 93% with the major contaminant, S100A12, making up 6%. For mass spectrometry and protein carbonyl experiments, calprotectin (40 M) was incubated with HNE (0 -800 M) in PBS at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Purification and Use of Calprotectin from Human Neutrophils-Calprotectin was purified from the cytosol of human neutrophils obtained by nitrogen cavitation using a previously described method (14) with Coomassie Blue staining of reducing SDS-PAGE gels indicating that the purity of calprotectin was 93% with the major contaminant, S100A12, making up 6%. For mass spectrometry and protein carbonyl experiments, calprotectin (40 M) was incubated with HNE (0 -800 M) in PBS at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…CP inhibits bacterial growth and metal-dependent virulence factors by sequestering Mn and Zn ions. However, the relative contribution of Mn vs. Zn sequestration and the corresponding effects on specific cellular pathways are unknown (11,13,20). To address this issue, the ΔS1 and ΔS2 CP mutants were used to assess the individual contributions of Mn and Zn sequestration to inhibiting S. aureus growth.…”
mentioning
confidence: 99%
“…In fact, examination of abscesses formed during S. aureus infection has revealed that these lesions are Mn and Zn depleted (14). It was subsequently determined that the Mnand Zn-binding S100 protein calprotectin (CP) is a critical component of this nutrient-withholding response (10,14,18,19). CPdeficient mice fail to remove Mn, but not Zn, from staphylococcal liver abscesses and have higher bacterial burdens during infection (14, 18).…”
mentioning
confidence: 99%